Charging and discharging at the nanoscale: Fermi level equilibration of metallic nanoparticles. Issue 5 (20th May 2015) - Scanlon, Micheál D.; Peljo, Pekka; Méndez, Manuel A.; Smirnov, Evgeny; Girault, Hubert H.
<x xml:space="preserve">Abstract</x> Surrounding environment, excess charge and size affect the Fermi level of the electrons in nanoparticles, having a significant influence on their properties.